The Experience Economy - Gilmore, James; Pine, B. (HighBridge, 1999)
Beyond the service economy of the last century is quietly emerging the next age of commerce, the experience economy. Joseph Pine and James Gilmore present a thought-provoking discussion and glimpse into the next evolution in the marketplace.